Intussusception in the adult - Sáez, Hugo; Fronzutti, Agustín; Melognio, Silvio; Mesa, Guillermo (Cirugía del Uruguay, 1975)
Three observations of intestinal intussusception in adults are reported; two of them were purely enterical and one was ileocolic. Ali of them -as it is most often seen in adults- were secondary to tumors of the small bowel: a submucous lipoma, a leiomyoma and a carcinod tumor. The rarity of the disease is remarked. Diagnosis is seldom performed in the preoperative stage. The treatment is surgical; intestinal resection is almost always required, either due to the importance of the lesions of the invaginated loop, or because reduction cannot be achieved, or because it is not possible to discard a malignant lesion.